Penggambaran Penyakit Mental pada Portal Berita Daring selama Pandemi Covid-19: Perbandingan pada Tempo.co dan Kompas.com - Raihan Sabili Izzati; Kunto Adi Wibowo; Ikhsan Fuady (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
Online news portals are widely accessed by the public to get various information. There are two online news portals that are well known by the Indonesian people, namely Tempo.co and Kompas.com. Since 2019, those two news portals have not stopped providing information about the Covid-19 pandemic, especially regarding mental illness due to the pandemic. By using framing theory, this study aims to find out how the differences in the representation of mental illness on Tempo.co and Kompas.com. This study uses quantitative content analysis method to analyze texts on online news portal. Sampling was carried out using probability simple random sampling technique during the PSBB period in Jakarta, from April 10 to June 4, 2020. A sample of 65 news articles on Tempo.co and 100 news articles on Kompas.com were taken based on six keywords, those are “penyakit mental”, “penyakit jiwa”, “gangguan mental”, “gangguan jiwa”, “kesehatan mental”, and “kesehatan jiwa”. Data were analyzed using nonparametric statistical calculations chi square contingency coefficient. The results showed that there were differences in the representation of danger-to-self characteristic on Tempo.co and Kompas.com, but there were no differences in the representations of causes, solutions, and tone of articles on Tempo.co and Kompas.com.